Potential Performance of Two New RT-PCR and RT-qPCR Methods for Multiplex Detection of Dengue Virus Serotypes 1–4 and Chikungunya Virus in Mosquitoes - Michel Kiréopori Gomgnimbou; Louis Robert Wendyam Belem; Etienne Bilgo; Miriam Félicité Amara; Zouera Laouali; Ali Ouari; Toussaint Bayala; Kobo Gnada; Raymond Kharlis Yao; Moussa Namountougou; Ibrahim Sangaré (Current Issues in Molecular Biology, 2024)
Mosquitoes of the genus Aedes are the most important arthropod disease vector. Dengue virus (DENV) and Chikungunya virus (CHIKV) are the main arboviruses distributed throughout the world. Based on entomo-virological surveillance, appropriate public health strategies can be adopted to contain cases and control outbreaks. This study aims to show the potential performance of two new molecular methods for detecting DENV serotypes and CHIKV in mosquitoes. Mosquitoes were collected in urban and sylvatic areas of Bobo-Dioulasso, Burkina Faso, between July and August 2023. DENV and CHIKV were screened using new multiplex RT-PCR and RT-qPCR methods. A total of 2150 mosquitoes were trapped, consisting of 976 Aedes (959 Ae. aegypti, 6 Ae. furcifer, and 11 Ae. vittatus) and 1174 Culex sp. These were grouped into 39 pools, with each pool containing a maximum of 30 mosquitoes. Molecular screening revealed that 7.7% (3/39) of the pools were positive for DENV. Specifically, DENV-1 was detected in one pool (1/3), and DENV-3 was found in two pools (2/3). All pools tested negative for CHIKV. The overall minimum infection rate (MIR) of DENV in this study was 3.07 (95% CI: 2.24–19.86). This study shows the usefulness of our new molecular tools for the surveillance of DENV serotypes and CHIKV.